Detection and treatment of subclinical tuberculosis - Robertson,BD; Altmann,D; Barry,C; Bishai,B; Cole,S; Dick,T; Duncan,K; Dye,C; Ehrt,S; Esmail,H; Flynn,J; Hafner,R; et al. (Tuberculosis, 2012)
Reduction of active disease by preventive therapy has the potential to make an important contribution towards the goal of tuberculosis (TB) elimination. This report summarises discussions amongst a Working Group convened to consider areas of research that will be important in optimising the design and delivery of preventative therapies. The Working Group met in Cape Town on 26th February 2012, following presentation of results from the GC11 Grand Challenges in Global Health project to discover drugs for latent TB.